Characterizing of dropouts in the mental health of refugees and asylum seekers (MEHIRA) study examining the effects of a stepped and collaborative care model - a multicentered rater-blinded randomized controlled trial - Kemna, Solveig; Bringmann, Max; Karnouk, Carine; Hoell, Andreas; Tschorn, Mira; Kamp-Becker, Inge; Padberg, Frank; Übleis, Aline; Hasan, Alkomiet; Falkai, Peter; Salize, Hans Joachim; Meyer-Lindenberg, Andreas; et al. (Psychological medicine, 2025)
BackgroundDropout from healthcare interventions can negatively affect patients and healthcare providers through impaired trust in the healthcare system and ineffective use of resources. Research on this topic is still largely missing on refugees and asylum seekers. The current study aimed to characterize predictors for dropout in the Mental Health in Refugees and Asylum Seekers (MEHIRA) study, one of the largest multicentered controlled trials investigating the effectiveness and cost-effectiveness of a nationwide stepped and collaborative care model.MethodsPredictors were multiply imputed and selected for descriptive modelling using backward elimination. The final variable set was entered into logistic regression.ResultsThe overall dropout rate was 41,7%. Dropout was higher in participants in group therapy (p = 0.001; OR = 10.7), with larger satisfaction with social relationships (p = 0.017; OR = 1.87), with difficulties in maintaining personal relationships (p = 0.005; OR = 4.27), and with higher depressive symptoms (p = 0.029; OR = 1.05). Participants living in refugee accommodation (p = 0.040; OR = 0.45), with a change in social status (p = 0.008; OR = 0.67) and with conduct (p = 0.020; OR = 0.24) and emotional problems (p = 0.013; OR = 0.31) were significantly less likely to drop out of treatment.ConclusionOverall, the outcomes of this study suggest that predictors assessing social relationships, social status, and living conditions should be considered as topics of psychological treatment to increase adherence and as predictors for future research studies (including treatment type).